Tracking Foreign Investors: Their Impact on Stock Price Volatility in the Indonesian Capital Market - Muhammad Mukhsin; Retno Cahyaningati; Mochammad Ilham Ramadhani; Melinda Yulia Agatha (Jurnal Bisnis dan Manajemen, 2025)
This study investigates the influence of foreign ownership on stock price volatility in the Indonesian capital market, with Return on Assets (ROA) as a mediating variable. The research aims to determine whether foreign investors contribute to market instability and whether company performance, as measured by ROA, plays a role in this relationship. The study employs panel data from 23 companies listed in the LQ45 index over the period 2020–2024. Analytical methods include panel regression tests, Chow and Hausman tests for model selection, and the Sobel test to assess mediation effects. Data were processed using EViews 13 and Microsoft Excel. The results indicate that foreign ownership does not significantly affect ROA, nor does ROA mediate the relationship between foreign ownership and stock price volatility. However, foreign ownership directly and significantly influences stock price volatility, suggesting that the presence of foreign investors may heighten market fluctuations. These findings imply that while foreign investors are vital for market liquidity and growth, their activities may also introduce volatility. Policymakers and regulators should consider mechanisms to balance foreign participation with market stability. Future research may explore additional mediating variables or extend the analysis to different market segments.